How Much Can a Smart Parking System Save You?. (October 2014) - Surpris, Glenn; Liu, Dahai; Vincenzi, Dennis
We conducted this study to investigate the effect of smart parking systems on parking search times in large parking lots. Smart parking systems are systems that provide real-time parking spot availability information to drivers. We used discrete event simulation to model a university parking lot and estimate how much time could be saved without physically implementing a system for experimentation. We found that smart parking systems can reduce search times by an average of 11 s. This shows potential for a multi-lot smart parking system that might save a larger amount of time and reduce harmful vehicle emissions.